Development – led marginalisation: a historical analysis of the Jahai in RPS Air Banun from the early 1900s to the 1980s - Ronzi Mohd Yusoff,; Sharina Abdul Halim,; Mustaffa Omar,; Joy Jacqueline Pereira,; Hood Salleh, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
The Jahai from RPS Air Banun are amongst the indigenous ethnics found in Peninsular Malaysia who still grapple below the stated level of poverty. Various efforts have been initiated with intentions of extracting them from their traditional ways of life in order to live on par amongst the multicultural – multiracial Malaysian population. Even so, fast paced development and urbanization has caused them to be left far behind when compared with their non-indigenous Malaysian counterparts. Despite extensive planning and implementation, development programmes have shown little success in changing their socio-economic status for the better and they have only been further marginalized and threatened by these initiatives. The deterioration in socio-economic status of the Jahai from RPS Air Banun is found to be closely related to the history of this nation’s development especially after achieving independence. Rapid urbanization and economic growth during the post-communist period had vastly changed the country’s physical landscape, thus changing the lives of the indigenous minority whose livelihood was still greatly dependant on natural resources. By employing the historical perspective, this paper examines the socio-economic status of the Jahai in RPS Air Banun who still live below the poverty level even after three decades of involvement in the Orang Asli Resettlement Programme.